EFFECT OF PRODUCT, QUALITY OF SERVICE, AND FACILITIES ON PATIENT SATISFACTION IN PUSKESMAS RANAI–NATUNA - Paradila Putri, Inggerit; Ngaliman, Ngaliman; Satriawan, Bambang (RADJA PUBLIKA, 2022)
The purpose of this research was to analyze the Patient santifaction at the Health Center Ranai – Natuna. This research uses the variables of products, service quality, and facilities to analyze the influence of patient santifaction. The population of this research are patient at the Health Center Ranai – Natuna. While the sample taken in this research were as many as 100 people drawn from the population. The collected data used questionnaire method is to provide a list of questions or questionnaires directly to respondents. The results showed that the R Squer value was 0.818 or 81.8% of this value. It can be seen that the product, service quality and facilities have an effect on patient satisfaction by 81.8% while the remaining 18.2% is influenced by other factors that are not examined. The results of the research based on the T test for the product had a significant value of 0.161, service quality was 0.308 and facilities were 0.489 and seen from the analysis of the coefficient of determination it was stated that the product, service quality, and facilities had an effect of 81.8% on patient satisfaction at the Health Center Ranai - Natuna.